2015
DOI: 10.1016/j.mechmat.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of viscoelasticity on heterogeneous stress fields at frictional interfaces

Abstract: a b s t r a c tWe investigate the evolution of heterogeneous stress states along frictional interfaces. Using finite-element simulations, we model the occurrence of precursory slip sequences on a deformable-deformable as well as a deformable-rigid interface between two solids. Every interface rupture creates a stress concentration at its arrest position and erases the stress concentrations produced by previous slip events. While the interface is sticking perfectly between two slip events, erased stress concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…After the current rupture, they are erased due to the linear slip-weakening friction law [see τ + r ] and will partially reappear over time. This effect was shown to be the result of the bulk's viscoelasticity [22,23].…”
Section: Modelmentioning
confidence: 99%
“…After the current rupture, they are erased due to the linear slip-weakening friction law [see τ + r ] and will partially reappear over time. This effect was shown to be the result of the bulk's viscoelasticity [22,23].…”
Section: Modelmentioning
confidence: 99%
“…As stated in Refs. ,, τ0 can be equated as τ0=σxy where σxy is effective stress at the particle interfaces in the xy plane (see Figure ). Then, eq.…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…In a detailed study of the transition from sub-Rayleigh to inter-sonic propagation at a onedimensional interface, Liu and Lapusta (2008) demonstrated that a single favorable heterogeneity leads to a secondary crack which accelerates to inter-sonic speeds with an abrupt jump from the Rayleigh wave speed to an inter-sonic speed. The emergence and evolution of increased pre-stress heterogeneities due to the arrest of preceding slip fronts was studied by Radiguet et al (2013Radiguet et al ( , 2015.…”
Section: Introductionmentioning
confidence: 99%